KAJIAN KONSEPTUAL PEMODELAN PERUBAHAN PENGGUNAAN LAHAN UNTUK STUDI ILMU LINGKUNGAN - Bokiraiya Latuamury (Jurnal Teknosains, 2013)
Modeling is one of the methods in the portfolio of techniques and approaches available to unravel the dynamics of the land-use system. In this perspective, models are used as a learning and communication tool between researchers to formalize knowledge on the dynamics of land-use change. Land-use system is a very complex system, such that computer modeling is needed as a computational laboratory to estimate and test hypotheses about the process of land-use change. One of the major difficulties in multi-disciplinary research is to find ways to express oneself, which are acceptable to all the disciplines involved and free from the connotation of any or all of them. Land-use change models play an important role in exploring possible future developments in the land-use system. This paper attempts to show the methods and approaches to be used as a communication and learning environment for stakeholders involved in the decision making about land-use change systems in the field of environment